White paper: Oncofertility in pediatric patients with Wilms tumor. Issue 6 (11th May 2022) - van der Perk, M. E. Madeleine; Cost, Nicholas G.; Bos, Annelies M. E.; Brannigan, Robert; Chowdhury, Tanzina; Davidoff, Andrew M.; Daw, Najat C.; Dome, Jeffrey S.; Ehrlich, Peter; Graf, Norbert; Geller, James; Kalapurakal, John; et al.
Abstract: The survival of childhood Wilms tumor is currently around 90%, with many survivors reaching reproductive age. Chemotherapy and radiotherapy are established risk factors for gonadal damage and are used in both COG and SIOP Wilms tumor treatment protocols. The risk of infertility in Wilms tumor patients is low but increases with intensification of treatment including the use of alkylating agents, whole abdominal radiation or radiotherapy to the pelvis. Both COG and SIOP protocols aim to limit the use of gonadotoxic treatment, but unfortunately this cannot be avoided in all patients. Infertility is considered one of the most important late effects of childhood cancer treatment by patients and their families. Thus, timely discussion of gonadal damage risk and fertility preservation options is important. Additionally, irrespective of the choice for preservation, consultation with a fertility preservation (FP) team is associated with decreased patient and family regret and better quality of life. Current guidelines recommend early discussion of the impact of therapy on potential fertility. Since most patients with Wilms tumors are prepubertal, potential FP methods for this group are still considered experimental. There are no proven methods for FP for prepubertal males (testicular biopsy for cryopreservation is experimental), and there is just a single option for prepubertal females (ovarian tissue cryopreservation), posing both technical and ethical challenges. Identification of genetic markers of susceptibility to gonadotoxic therapy may help to stratify patient risk of gonadal damage and identify patients most likely to benefit from FP methods. Abstract : What's new? Wilms tumor (WT), a childhood kidney cancer, has a survival rate of around 90%. Because most patients survive to reproductive age, treatment decisions must take into account the risk of gonadal damage. Discussing infertility risk and fertility preservation (FP) is associated with decreased patient and family regret and better quality of life. Here, the authors present an overview of the evidence regarding the future fertility after WT treatment, collected through a unique global collaboration between Children's Oncology Group (COG) and Societe Internationale D'oncologie Pediatrique (SIOP). They describe options for FP as well as ethical and genetic considerations, which may guide personalized risk prediction and selection of patients at risk of chemotherapy or radiotherapy induced gonadal impairment.